Answer:
The expanded value of the given expression is
[tex](3a^4b)(5ab^2)-(a^5b^2)(9b)=6a^5b^3[/tex]
Step-by-step explanation:
Given expression is
[tex](3a^4b)(5ab^2)-(a^5b^2)(9b)[/tex]
To find the value of the given expression:
[tex](3a^4b)(5ab^2)-(a^5b^2)(9b)=15a^5b^3-9a^5b^3[/tex]
(By multiplying the products and doing algebraci subtracion of the above expression)
Now taking the common terms in the above equation we get
[tex](3a^4b)(5ab^2)-(a^5b^2)(9b)=3a^5b^3(5-3)[/tex]
[tex]=3a^5b^3(2)[/tex]
[tex]=6a^5b^3[/tex]
Therefore the expanded value of the given expression is
[tex](3a^4b)(5ab^2)-(a^5b^2)(9b)=6a^5b^3[/tex]